Broadcast announcing worktext : a media performance guide - Stephenson, Alan R. 4 0 16; Reese, David E.,;Beadle, Mary E.; 5 (Amsterdam : Focal Press, 2009)
Looks at broadcast announcing, focusing on the audio performance environment, the television performance environment, vocal development, and other topics.
Previous ed.: 2005.;Includes index.
Adult;Adult.
System requirements not stated.
Keywords: 2 -- 0; 6; Radio announcing.;Television announcing.;Radio broadcasting.;Television broadcasting; 20; 2